Fishing on Facebook: Using Social Media and Citizen Science to Crowd-Source Trophy Murray Cod - Matthew O’Connell; Dirk Spennemann; Jennifer Bond; R. Keller Kopf; Nicole McCasker; Paul Humphries (Citizen Science: Theory and Practice)
Shifting baselines, whereby people’s perceptions of what was the “natural” state of the environment changes with each generation, hinders conservation, restoration, and management. Formal and informal historical animal records can be used to inform past biological, ecological, and environmental patterns and processes. Trophy specimens are cultural and social objects but also are examples of informal historical records that may supply biological tissue and supplement formal natural history collections. The use of social media to gather information from citizen scientists has great potential for data collection of such specimens. The aim of this study was to evaluate the potential utility of Facebook and traditional media to collect data on taxidermal Murray cod (Maccullochella peelii), a large, long-lived freshwater fish endemic to the Murray-Darling Basin, Australia. A Facebook group, “Cod Spot,” was established as the location for information dissemination to potential citizen scientists, and where data on Murray cod mounts could be uploaded. This was complemented with social and mainstream media promotion, a research website, and an e-survey. Cod Spot received >7,000 interactions and approximately 400 participants. A total of 189 verified locations of Murray cod head and whole mounts were found. The e-survey provided verification of the potential to turn these cultural and social objects into ones with scientific value. Participants included interested persons, collectors, taxidermists, stewards, or owners of mounts. Most participants were males aged 35+, although women comprised almost a third of website users. This research has shown that low-cost marketing, combined with a widely dispersed, relatively common and well-known object of interest, can be effective at gaining participation in citizen science collaborations.